Exposer la sculpture dans l’Albertinum de Dresde : passé, présent et futur - Astrid Nielsen (Les Cahiers de l'École du Louvre)
After four years of renovation, the Albertinum of Dresden reopened its doors in 2010. With a completely new layout of the sculpture collection and the gallery of new masters of the Dresden state collections, the building exhibits works of art from the Romantic period to the present. The development of this new concept is largely the result of the decision to install the classical collection, which had been kept in the Albertinum since 1894, in the west hall of the building of the galleries of Gottfried Semper in the Zwinger in Dresden beginning in 2018. This contribution provides a brief look at the history of the sculpture collection in the Albertinum and details the development of the conception of the exposition for the works in the sculpture collection and envisages the future prospects of the museum.